Implementasi Strategi PAIKEM GEMBROT Pada Pembelajaran Bahasa Arab di SMP Muhammadiyah 1 dan 8 Surakarta - Afiffah Ragilia, Nur; Mahasri Shobahiya; Triono Ali Mustofa (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The PAIKEM GEMBROT strategy is a teaching approach that emphasizes Active, Innovative, Creative, Effective, and Enjoyable Learning, as well as Joyful and Substantive Learning. The implementation of this strategy in Arabic language learning aims to increase students' interest and motivation, as well as optimize their learning outcomes. The purpose of this research is to analyze the implementation of the PAIKEM GEMBROT strategy in Arabic language learning at SMP Muhammadiyah 1 and 8 Surakarta. The research method used is qualitative with a field study approach. The results obtained are: 1) The PAIKEM GEMBROT strategy implemented in Arabic language learning at SMP Muhammadiyah 1 Surakarta includes methods such as information search, reading aloud, small group discussion, and singing. 2) The PAIKEM GEMBROT strategy is also implemented in Arabic language learning at SMP Muhammadiyah 8 Surakarta with methods such as reading aloud, Q&A, and Index Card Match. 3) The challenges faced in implementing the PAIKEM GEMBROT strategy at SMP Muhammadiyah 1 Surakarta include limited teaching time and students' inadequate Quran reading skills. Meanwhile, the challenges faced at SMP Muhammadiyah 8 Surakarta include inadequate facilities, unstable Wi-Fi signals, limited internet quotas for students, and students' lack of basic understanding of Arabic lessons from public elementary schools (SDN).